EFFCTIVENESS OF E-SUMMON IN CONTACTING ABSENT PARTIES AT TULANG BAWANG RELIGIOUS COURT - Lena; Riyan Erwin Hidayat (Familia: Jurnal Hukum Keluarga, 2025)
This research uses a field research method with a legal and descriptive-analytical approach, with primary data obtained from interviews and secondary data from legal documents and legislation. The summoning of parties in cases at the Religious Court is an important process in the settlement of cases, including absent cases such as divorce with parties whose whereabouts are unknown. In this context, the application of e-summon technology (electronic summoning) is expected to increase the effectiveness of summoning. This study aims to evaluate the effectiveness of the application of e-summons in absentia cases in the Tulang Bawang Religious Court using Campbell's (1970) theory of effectiveness, which includes four indicators: time efficiency, cost efficiency, accuracy of targets, and quality of service outcomes. This study uses a field research method with a juridical and descriptive-analytical approach, with primary data derived from interviews and secondary data from legal documents and legislation. The research results show that e-summons via website is more efficient in terms of time and cost compared to conventional methods, although there are still constraints on access to information by the defendant, which impacts the full realization of procedural justice.